Optimization of Rapid Solidification to Enrich Fish Oil from by-Product of Lemuru Canning Processing with w-3 batty Acids by Response Surface Method - Teti Estiasih; Fithri Choirun Nisa; Kgs Ahmadi; Umiatun . (Jurnal Teknologi dan Industri Pangan, 2005)
Oil from by-product of lemuru canning processing was a source of w-3 fatty acid but its characteristics had out been known. The content of w-3 fatty acids of this oil had to be increased. Various methods are available to enhance w-3 fatty acids concentration Rapid solidification was one of limited methods to enrich fish oil by w-3 fatty acids containing triglycerides. This research was conducted to optimize rapid solidification condition to enrich fish oil from by product of lemuru canning processing with w-3 fatty acids and characterize the enriched oil compared by International Association of Fish Meal and Oil Manufacturers standard. In optimization process, the content of EPA+OHA and yield .was maximized. A two-factors central composite design in Response Surface Method was used to study the effect of solvent-to-oil ratio (X1) and extraction time (X2). The response (Y) is the multiplication of EPA+DHA content by yield. The results showed that under optimum conditions the maximum response were obtained at a solvent-to-oil ratio of 3,95:1(vw) and extraction time of 24,93 hours. The w-3 fatty acids enriched fish oil had EPA+DHA content of 33,33% and yield of 9.40% (w/w). The produced w-3 fatty acids enriched fish oil had good quality based on food grade fish oil standard, unless Fe and Cu content. Chelation could reduce these oxidizing metals. Key words : w-3 fatty acids, rapid solidification, response surface method, central composite design.